1999
DOI: 10.1128/jb.181.1.347-352.1999
|View full text |Cite
|
Sign up to set email alerts
|

APT1 , but Not APT2 , Codes for a Functional Adenine Phosphoribosyltransferase in Saccharomyces cerevisiae

Abstract: The yeast Saccharomyces cerevisiae has two separate genes (APT1 and APT2) that encode two potentially different forms of adenine phosphoribosyltransferase (APRT). However, genetic analysis indicated that only APT1could code for a complementing activity. Cloning and expression of both the APT1 and APT2 genes in Escherichia coli showed that although discrete proteins (APRT1 and APRT2) were made by these genes, only APRT1 had detectable APRT activity. Northern and Western blot analyses demonstrated that onlyAPT1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…A third resistance mechanism is to interfere with activation of the drug, and it is possible that APT2 could act in this way. Our finding that APT2 overexpression confers resistance to HAP is surprising since previous studies did not detect a knockout phenotype or enzymatic activity associated with APT2 , which was therefore proposed to be a pseudogene [ 37 ]. The homology to APT1 which encodes APRT suggests that APT2 , if active, should encode an enzyme with similar activity.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…A third resistance mechanism is to interfere with activation of the drug, and it is possible that APT2 could act in this way. Our finding that APT2 overexpression confers resistance to HAP is surprising since previous studies did not detect a knockout phenotype or enzymatic activity associated with APT2 , which was therefore proposed to be a pseudogene [ 37 ]. The homology to APT1 which encodes APRT suggests that APT2 , if active, should encode an enzyme with similar activity.…”
Section: Discussionmentioning
confidence: 73%
“…However, Apt2p lacks APRT activity when expressed in E . coli and a disruption of the APT2 gene has no apparent phenotype in yeast [ 37 ]. It is thus not clear what enzymatic activity, if any, that Atp2p possesses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4A). This level of inhibition of TBSV repRNA accumulation might not be significant, because over-expression of a pseudogene (APT2), which has no enzymatic activity when expressed (Alfonzo et al, 1999), also led to reduced TBSV repRNA accumulation (63.7 ± 15.9%), suggesting that two-fold or less reduction might be due to the reduced ability of yeast cells to support repRNA accumulation under the protein over-expression condition. Together, the above experiments indicated that over-expression of 40% of the 45 RNA-binding host proteins could affect TBSV repRNA accumulation in yeast.…”
Section: Effect Of Over-expression Of Selected Host Proteins On Tbsv mentioning
confidence: 99%
“…Mutations affecting adenine phosphoribosyl transferase (APRT) and hypoxanthine-guanine phosphoribosyl transferase (HGPRT) in S. cerevisiae have been described previously (10,12,13). APRT is encoded by the APT1 gene (2), while APT2, a gene encoding a putative PRT highly similar to Apt1p, has been reported (14), although no enzymatic activity could be associated with this protein (1). HGPRT is encoded by the HPT1 gene (6).…”
mentioning
confidence: 99%